Effect of Quantity of Low–Methoxyl Pectin on Physical Properties of Freeze–Dried Strawberry Jellies - Ciurzyńska Agnieszka; Lenart Andrzej; Karwosińska Joanna (Polish Journal of Food and Nutrition Sciences)
The development of fruit-based products with a high proportion of fruit and good nutritional, sensory and functional properties may help to diversify market supply. These products ought to be attractive, especially to young people, easy to consume and have a reasonably long shelf life. Three recipes of freeze-dried strawberry jelly with low-methoxyl pectin (LMP) (2.0, 2.5, 3.5% LMP) with the use of strawberry pulp were obtained and physical properties were investigated to choose the sample with the best quality factors. The quantity of added low-methoxyl pectin influences the physical properties of freeze-dried strawberry jellies. The recipe with 2.5% addition of low-methoxyl pectin was chosen based on the results obtained. Despite the relatively high friability and low hardness, and higher shrinkage, it has a fast rate of rehydration. It is also characterised by high porosity and the parameters of the colour most similar to the raw material and low water content and activity.